R-branch line intensities and temperature-dependent line broadening and shift coefficients of the nitric oxide fundamental rovibrational band. (December 2019) - Almodovar, Christopher A.; Su, Wey-Wey; Strand, Christopher L.; Hanson, Ronald K.
Highlights: Measured the temperature dependence of pressure broadening and shift coefficients for over 40 transitions in the R-branch of the NO fundamental rovibrational band from 294 to 802 K. Temperature range of experiments extended through high temperature 1000–2500 K shock tube experiments. Measured line intensities agree well with HITRAN databases. Measured the line intensities and pressure broadening coefficients of several v ′ ← v ″ = 2 ← 1 hot band transitions. The insufficiency of the temperature-dependent power law for pressure broadening coefficients outside the temperature range studied is demonstrated. Abstract: Two quantum cascade lasers were used to measure line intensities and line shape parameters of nitric oxide rovibrational transitions in the R-branch of the fundamental band near 1900 cm − 1 in a heated static cell with temperatures from 294 to 802 K and in a shock tube from 1000 to 2500 K. Pressure in the static cell and shock tube experiments ranged from 0.025 to 1 atm and 1.5 to 3.2 atm, respectively. Collision broadening and pressure shift coefficients along with their temperature dependence were determined for nitrogen, argon, and air collision partners. The line shapes of high J" rovibrational transitions (i.e. R(39.5)–R(43.5)) were measured for the first time at elevated temperatures, where these transitions become sufficiently strong. Additionally, several hot band transitions were measured. Measured line intensities show good agreement with those measured by other researchers and tabulated in the HITRAN databases. Comparisons between the temperature exponents measured in the static cell and shock tube provide evidence that the power law often used to define the temperature dependence of collisional effects does not hold outside the temperature range studied.